QUESTION: For f(x)=x+3 and g(x) =2x+5, find the following
a. (fog)(x)=
b. (gof)(x)=
c. (fog)(-1)=

ANSWER: What I believe that symbol is the same as is (fog)(x) = f(g(x)).
Is that correct?
This means we have
a. f(g(x)) = g(x) + 3, so it is 2x + 5 + 3 = 2x + 8.
b. g(f(x)) = 2*f(x) + 5 = 2(x+3) + 5 = 2x + 6 + 5 = 2x + 11.
c. f(g(-1) = f(2(-1)+5) = f(-2+5) = f(3) = 3+3 = 6.

---------- FOLLOW-UP ----------

QUESTION: Evaluate the function at the given values of the independent variable and simplify.
a. f(3)
b. f(-3)
c. f(-x)

If that suppose to be 4x-1/x?
That is, are both x's squared?

a. Put in 3 as x and get 4*9 - 1/9 = 323 8/9.
b. Put in -3 as x and get the same thing,  since when squared the -3 still gives a 9.
c. When putting in a negative the answer is  the equation 4x-1/x since a negative squared is still positive.  That is, x = (-x).


All Answers

Answers by Expert:

Ask Experts


Scott A Wilson


Any algebraic question you've got. That includes question that are linear, quadratic, exponential, etc.


I have solved story problems, linear equations, parabolic equations. I have also solved some 3rd order equations and equations with multiple variables.

Documents at Boeing in assistance on the manufacturiing floor.

MS at math OSU in mathematics at OSU, 1986. BS at OSU in mathematical sciences (math, statistics, computer science), 1984.

Awards and Honors
Both my BS and MS degrees were given with honors.

Past/Present Clients
Students in a wide variety of areas since the 80's; over 1,000 of them have been in algebra.

©2016 All rights reserved.